A COMPARİSON BETWEEN HAİKU, POETRY POSTERS AND SE-KHESHTI İN KURDİSH POETRY İN SOUTH AND EAST KURDİSTAN - Mohammed, Dilkhwaz; Abdullah, Halima (Humanities Journal of University of Zakho, 2025)
Short poetry is one of the most important means of expression in world literature, the brevity of the poem and the depth of its meanings attract readers Short poetry in Kurdish literature has a long history. Some of the styles of short poetry are as follows: the single verse, the dubayt and the quatrain. etc. The demand for these poetic styles continues to this day, and many poets are still interested in these poems, albeit with a modern approach. From this standpoint, this research(A comparison between Haiku, Poetry Posters and Se-Kheshtı in Kurdish Poetry in South and East Kurdistan) is based on a comparison between three different forms of poems: haiku, Poetry Posters and Se-Kheshtı in Kurdish poetry. Based on the texts of a group of poets, the research aims to understand the world of meanings, connotations, structure, and specific form of each type of poem and to state its results. Taking into account the haiku poem's intermingling with different types of literature, this research will focus on the similarities and differences between them. To better clarify this issue, we will shed light on each of the three forms of poems we have identified, and answer some questions: Does each have its own culture and philosophy? And how can we distinguish between haiku and other forms of short poems? Based on these hypothetical questions, we reached a number of conclusions that highlight the differences and commonalities between these types of short poetry. The results of this research demonstrate that each of the haiku, Poetry Posters and Se-Kheshtı has its own distinct culture and philosophy. Although brevity is a common feature among the three poetic genres, haiku differs from the other two in that the poet must be neutral in conveying images and refrain from expressing his feelings indirectly.